2021
DOI: 10.1186/s13229-021-00470-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction learning in adults with autism and its molecular correlates

Abstract: Background According to Bayesian hypotheses, individuals with Autism Spectrum Disorder (ASD) have difficulties making accurate predictions about their environment. In particular, the mechanisms by which they assign precision to predictions or sensory inputs would be suboptimal in ASD. These mechanisms are thought to be mostly mediated by glutamate and GABA. Here, we aimed to shed light on prediction learning in ASD and on its neurobiological correlates. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 105 publications
5
33
0
Order By: Relevance
“…MRS studies in adults with ASD reported no significant GABA concentration differences (Ajram et al, 2017; Horder et al, 2018; Kirkovski et al, 2018) or increased GABA levels (Fung et al, 2021) in frontal and prefrontal areas compared to NTC. With regard to Glu or Glx concentrations, increased (Sapey‐Triomphe et al, 2021) as well as similar Glu or Glx concentrations (Ajram et al, 2017; Endres et al, 2015; Horder et al, 2013, 2018) have been reported in the frontal or prefrontal cortex of adults with ASD.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…MRS studies in adults with ASD reported no significant GABA concentration differences (Ajram et al, 2017; Horder et al, 2018; Kirkovski et al, 2018) or increased GABA levels (Fung et al, 2021) in frontal and prefrontal areas compared to NTC. With regard to Glu or Glx concentrations, increased (Sapey‐Triomphe et al, 2021) as well as similar Glu or Glx concentrations (Ajram et al, 2017; Endres et al, 2015; Horder et al, 2013, 2018) have been reported in the frontal or prefrontal cortex of adults with ASD.…”
Section: Introductionmentioning
confidence: 94%
“…According to the E/I imbalance theory, this imbalance between excitatory and inhibitory neurotransmission is reflected in an increase in glutamatergic (excitatory) and a decrease in GABAergic (inhibitory) signaling (Rubenstein, 2010; Rubenstein & Merzenich, 2003). However, with respect to glutamate, both a hypoglutamatergic and a hyperglutamatergic theory has been proposed (Eltokhi et al, 2020; Sapey‐Triomphe et al, 2021). Based on animal studies in which hypoglutamatergic animals exhibited autistic behavior, the hypoglutamatergic hypothesis of ASD has been postulated (Carlsson, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though most of the Bayesian and predictive coding models of autism were initially used to describe low-level sensory perception among autistic individuals, they may be applicable to high-level cognitive processes in autism such as learning of statistical regularities and associations as well as prediction and decision-making. Some studies reported that relative to neurotypical individuals, autistic individuals showed differential neural responses to statistical learning of a continuous auditory stream (Scott-Van Zeeland et al, 2010a , 2010b ; Wagley et al, 2020 ) and poorer learning of cue-outcome associations that are needed to make accurate predictions across various paradigms (Amoruso et al, 2019 ; Fogelson et al, 2019 ; Greene et al, 2019 ; Lawson et al, 2017 ; Sapey-Triomphe et al, 2021a , 2021b ), pointing to difficulties autistic individuals may have with extracting regularities from the input and having higher precision to prediction errors. Those models have also been used to understand whether learning differs when the environment changes, which is typically assessed using a probabilistic reversal learning task: learners first learn the contingencies of two cues and their outcomes over many trials (e.g., Cue A is associated with a reward at an 80:20 reinforcement schedule) after which the contingencies change (e.g., now Cue B rewards at an 80:20 reinforcement schedule).…”
mentioning
confidence: 99%